Review of Extensor Mechanism Injuries in the Dislocated Knee - Okoye, Munachukwudi; Wissman, Abigail; Wissman, Robert D. (The Journal of Knee Surgery, 2022)
Knee dislocations, aka multiligamentous injuries, are uncommon but devastating injuries often following high-energy trauma. Tears of the major knee stabilizers are well documented; however, injuries of the knee extensor mechanism are less commonly reported. The extensor mechanism is comprised of the patella, patellar tendon, and quadriceps tendons. Magnetic resonance imaging (MRI) is the preferred imaging modality of internal derangements of the knee due to its excellent soft tissue contrast. In this article, we will discuss the normal imaging findings of the extensor mechanism and review abnormalities following knee dislocation.
Keywords: knee dislocation; extensor mechanism; magnetic resonance imaging